Prognostic value of quantitative PET/CT in patients with a nonsmall cell lung cancer and another primary cancer. Issue 2 (February 2017) - Zhu, Xuee; Liao, Chuanhong; Penney, Bill C.; Li, Feng; Ferguson, Mark K.; Simon, Cassie A.; Wu, Tianming; Liu, Haiyan; Pu, Yonglin
Abstract : Objective: The staging and management of patients with newly diagnosed nonsmall cell lung cancer (NSCLC) in the setting of recently diagnosed other (metachronous or synchronous) primary cancer are challenging. This retrospective cohort study was carried out to test our hypothesis that baseline 2-deoxy-2-[ 18 F]fluoro-D-glucose ( 18 F-FDG) PET/CT parameters, including whole-body metabolic tumor volume (MTVWB ), total lesion glycolysis (TLGWB ), and maximum standardized uptake value (SUVmaxWB ), are associated with the overall survival (OS) of such patients. Patients and methods: A total of 110 NSCLC patients (52 men and 58 women, aged 68.6±7.8 years) with other primary malignant cancers who had baseline 18 F-FDG PET/CT scans were retrospectively reviewed. MTVWB, TLGWB, and SUVmaxWB were measured. Kaplan–Meier analysis with the log-rank test and Cox regression models were used to assess the association of OS with 18 F-FDG PET/CT parameters and clinical risk factors. Results: Kaplan–Meier analysis and univariate Cox regression models showed significant associations of OS with ln(MTVWB ), ln(TLGWB ), ln(SUVmaxWB ), TNM stage, and treatment type (surgery vs. no treatment). Multivariable Cox regression models showed a significant relationship of OS with ln(MTVWB ) [hazard ratio (HR)=1.368, P =0.001], ln(TLGWB ) (HR=1.313, P <0.001), and ln(SUVmaxWB ) (HR=1.739, P =0.006), adjusted for age, treatment type, tumor histology, and TNM stage. The TNM stage was not associated significantly with OS when MTVWB, TLGWB, or SUVmaxWB were included in the multivariable models. Conclusion: MTVWB, TLGWB, and SUVmaxWB from baseline 18 F-FDG PET/CT are associated individually with OS of patients with both NSCLC and other primary malignant tumors independent of age, treatment type, tumor histology, and TNM stage.